CYBERLOAFING MECHANISM: THE IMPACT OF WORKLOAD, SELF-CONTROL, AND JOB STRESS ON CIVIL SERVANT PERFORMANCE - Rizky, Roisman; Puji Lestari, Etty; Wihadanto, Ake (Universitas Islam Lamongan, 2024)
How influential are workload, self-control, and job stress on performance, considering cyberloafing as a mediating variable? The research method uses quantitative descriptive analysis techniques based on secondary and primary data obtained through questionnaires with a Likert scale approach. This study uses the SmartPLS version 4.1 analysis tool with PLS-SEM. The results of the study Workload, self-control have a positive and significant effect on performance, stress has a negative and significant effect on performance, then workload, self-control have a negative and significant effect on cyberloafing, while work stress has a positive and significant effect on cyberloafing, cyberloafing has a negative and significant effect on performance, cyberloafing significantly mediates the effect of workload on performance, cyberloafing significantly mediates the effect of self-control on the performance of civil servants, and cyberloafing significantly mediates the effect of stress on performance.